2022
DOI: 10.1101/2022.11.19.517212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic broadband noise increases the fitness of a freshwater zooplankton

Abstract: Although there is an increasing interest in the effects of anthropogenic noise on animals, aquatic studies mainly focus on organisms with hearing systems (marine mammals, fish, great arthropods) while many others of substantial ecological importance are not considered. Here we show that the water flea Daphnia magna, a widespread zooplankton species serving as food source for higher trophic levels, could be affected by noise pollution in a way that we did not expect. We found that isolated individuals exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 82 publications
(150 reference statements)
1
13
5
Order By: Relevance
“…We did not observe any effect of chronic boat noise exposition on Daphnia magna fecundity or survival. These results are opposite to Prosnier et al’s one (2022), where an exposition to a continuous broadband noise leads to a surprising increase of individuals’ fitness. This contradiction suggested that the effect of chronic noise pollution, on zooplankton species, could depend on the structure of noise.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…We did not observe any effect of chronic boat noise exposition on Daphnia magna fecundity or survival. These results are opposite to Prosnier et al’s one (2022), where an exposition to a continuous broadband noise leads to a surprising increase of individuals’ fitness. This contradiction suggested that the effect of chronic noise pollution, on zooplankton species, could depend on the structure of noise.…”
Section: Discussioncontrasting
confidence: 62%
“…For the smaller organisms, like zooplankton, little is known about the important of sound pattern. Here, the comparison with Lara & Vasconcelos (2021) and Prosnier et al (2022) suggest that patterns should also be considered in understanding the noise effects, with higher effect with a continuous noise.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations